1994
DOI: 10.1002/pen.760341409
|View full text |Cite
|
Sign up to set email alerts
|

Melt crystallization kinetics of syndiotactic polystryrene

Abstract: The crystallization kinetics of syndiotactic polystyrene (SPS) were studied using nonisothermal DSC analysis. Crystallization rates and half‐times were determined from the glass transition temperature (∼ 100°C) up to the melt temperature (∼ 270°C) for various molecular weight SPS polymers. The results suggest that the crystallization rate of SPS is molecular weight dependent. These results are also compared with previously determined crystallization kinetics of high density polyethylene. The maximum crystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…In miscible crystallizable/noncrystallizable blend systems, crystallization occurs only when the concentration of the noncrystallizable component is less than 50 wt %. 9,19,23 From the data fitting of the nonisothermal crystallization of SPS, 26 which shows the maximum T c at a fast cooling rate to be below 200°C, we believe that the crystallizations of SPS/APS blends were finished before reaching this temperature because all the crystallizations in our experiments were finished at least around 230°C. Thus, it can be said that although APS retarded the crystallization of SPS, the ultimate crystallinity did not change.…”
Section: Resultsmentioning
confidence: 99%
“…In miscible crystallizable/noncrystallizable blend systems, crystallization occurs only when the concentration of the noncrystallizable component is less than 50 wt %. 9,19,23 From the data fitting of the nonisothermal crystallization of SPS, 26 which shows the maximum T c at a fast cooling rate to be below 200°C, we believe that the crystallizations of SPS/APS blends were finished before reaching this temperature because all the crystallizations in our experiments were finished at least around 230°C. Thus, it can be said that although APS retarded the crystallization of SPS, the ultimate crystallinity did not change.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the nucleation rate was very fast and, in fact, faster than the rate for isotactic polystyrene (iPS). Wesson 6 studied the nonisothermal crystallization kinetics of sPS samples with a variety of molecular weights with differential scanning calorimetry (DSC). The results suggested that the crystallization rate depended on the molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…The last monomer into the chain controls the positioning of next monomer coordinating and directing it in such a way that the next insertion will be racemic to the last. [1] The syndiotactic configuration of the backbone provides a new material such that the polymer is able to crystallize at a relatively high rate [4,5] and form well structured spherulitic morphology when quiessently crystallized from the melt. [6±8] These crystalline structures and morphologies give rise to a new material with unique properties that is now finding its way in to applications in automotive parts under the hood, electronic connectors and electrical devices.…”
mentioning
confidence: 99%